(untitled) (Journal of Dhaka Medical College, 2010)
Organ transplantations have caused profound changes in saving the life in current days. Also raised several questions in the legal and ethical ground. In this paper we discussed legal considerations, donation procedures, death determination, diagnosis of brain death and organ transplantation act of Bangladesh. Key words: Legal guideline; organ transplantation; therapeutic tissue removal. DOI: 10.3329/jdmc.v18i2.6282 J Dhaka Med Coll. 2009; 18(2) : 174-177